2017
DOI: 10.1080/10942912.2016.1263863
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite profiling, antioxidant activity, and glycosidase inhibition property of the mesocarp tissue extracts of sugar date palm [Phoenix sylvestris(L.) Roxb.] fruits

Abstract: View related articles View Crossmark data Citing articles: 5 View citing articles Metabolite profiling, antioxidant activity, and glycosidase inhibition property of the mesocarp tissue extracts of sugar date palm [Phoenix sylvestris (L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Hydroxybenzoic acid ( m/z 137.0242) and hydroxybenzoic hexose ( m/z 299.0070) have already been characterized in jelly palm by Hoffmann, Carvalho, Barbieri, Rombaldi and Chaves [21]. The NaOH hydrolysed sugar date palm fruits also showed the presence of hydroxybenzoic acid derivatives ( m/z 253.9) in ethyl acetate extract [31]. Compound 7 in jelly palm fruit and compound 10 in fishtail palm fruit yielding [M − H] − ion at m/z at 315.0731 and 153.0200 respectively, were tentatively identified as protocatechuic acid 4- O -glucoside and protocatechuic acid (Table 2 and Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydroxybenzoic acid ( m/z 137.0242) and hydroxybenzoic hexose ( m/z 299.0070) have already been characterized in jelly palm by Hoffmann, Carvalho, Barbieri, Rombaldi and Chaves [21]. The NaOH hydrolysed sugar date palm fruits also showed the presence of hydroxybenzoic acid derivatives ( m/z 253.9) in ethyl acetate extract [31]. Compound 7 in jelly palm fruit and compound 10 in fishtail palm fruit yielding [M − H] − ion at m/z at 315.0731 and 153.0200 respectively, were tentatively identified as protocatechuic acid 4- O -glucoside and protocatechuic acid (Table 2 and Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…In the fishtail palm fruit, 5-(3’,5’-dihydroxyphenyl)-γ-valerolactone 3- O -glucuronide ([M + H] + m/z 385.1136) and 5-(3’,4’,-dihydroxyphenyl)-γ-valerolactone ([M − H] − m/z 207.0667) were detected (Table 3). Previously, there was no report demonstrating the detection of hydroxyphenylacetic, hydroxyphenylpentanoic and hydroxyphenylpropanoic acids in both jelly and fishtail palm fruits despite 3,4-dihydroxyphenylacetic acid reported in ethyl acetate extract of date palm fruits after alkaline processing [31].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we found molecules of phenolic acids in both seed and flesh, such as 4-hydroxybenzoic acid, which has previously been reported for the mesocarp tissue extracts of sugar date palm [ Phoenix sylvestris (L.) Roxb.] [ 51 ]. In addition, gentisic acid, which was only found in seeds, is considered an aspirin metabolite and is found naturally in the roots of the genus Gentiana and in the fungus penicillium brevicompactum [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, sugar date palm fruit ( Phoenix sylvestris (L.) Roxb.) extract inhibited α-glucosidase with an IC 50 value of 3.18 µg/mL [ 34 ], suggesting the potential use of date palm fruit against diabetes through α-glucosidase inhibition. Similar results were observed with low DPP-IV inhibitory activity detected in SO flesh, while none was found in CO flesh, suggesting that phenolics might not act as effective DPP-IV inhibitors.…”
Section: Discussionmentioning
confidence: 99%